Collaborative governance for community activation - KWON, Hee Kyung (KDI School, 2022)
The Seoul Metropolitan Government has been promoting a Management-Type Residential Environment Improvement Project that comprehensively improves the residential environment of low-rise residential areas through collaborative governance supporting community activation. However, a recent shift in the urban regeneration paradigm in Seoul has raised questions about collaborative governance as a tool for resident participatory planning in urban planning and management. This study focuses on the collaborative governance supporting community activation in the management-type residential environment improvement project through the example of Gomdallaekkum Maeul in Sinwol 1-dong, Yangcheon-gu, Seoul. Especially, Gomdallaekkum Maeul’s community organization shows evidence of establishing a virtuous cycle of public-private partnerships and collaboration between local networks in the COVID-19 pandemic period where community activities are restricted. Therefore, based on the case of reinforcement and extension of collaborative governance following the interaction of the unique community activation of Gomdallaekkum Maeul, a new perspective on the management-type residential environment improvement project is presented.
Thesis(Master) -- KDI School: Master of Development Policy, 2022
Keywords: City planning--Korea (South); Urban renewal--Korea (South)